Prevalence and Factors Associated with Intestinal Parasitic Infections among School Children in Sauka and Non-Sauka Communities of Darchula, Nepal (Tribhuvan University Journal of Microbiology, 2024)
Objective: To determine the prevalence of intestinal parasitic infections among the school children of Sauka and non Sauka communities of Khalanga, Darchula, Sudurpaschim Province, Nepal.Methods: This was a cross-sectional study conducted among school children from Sauka and non Sauka communities in Darchula district of Nepal. Stool samples were processed by using formal-ether sedimentation technique followed by normal saline and Iodine wet mount methods. Identification of parasites and/or ova in the stool samples was performed by microscopy.Results: The overall prevalence of parasitic infection was 21.3% (74/348), with significantly higher in males (28.3%) than females (16.3%) (p = 0.01). Sauka children exhibited a significantly higher prevalence (26%) of parasitic infection compared to non Sauka (14.9%) (p = 0.02). Lack of toilet at home, occupation, hand washing habits, and anti-helminthic drug use were significantly associated with infection. Monoparasitism (17.8%) dominated over multi parasitism (3.4%), with protozoan (21.6%) more prevalent than helminthes (3.2%). Giardia lamblia (9.2%) and Trichuris trichiura (1.4%) were the most prevalent protozoan and helminthic parasites, respectively.Conclusions: High prevalence of parasitic infection in the Sauka community indicates poor health hygiene and socio-economic status. It is high time to implement effective programs including awareness, anti-parasitic drugs distribution, and sanitation and hygiene improvement in this remote community.